Article PERSPEKIF TEORI BELAJAR SOSIAL DALAM MENGIMPLEMENTASI METODE PEMBELAJARAN LEARNING TOGETHER (LT) DALAM PEMBENTUKAN KEMAMPUAN MERESENSI DAN MENULIS TEKS RESENSI CERPEN - Semuel Nitbani (Jurnal Lazuardi, 2019)
Learning by using the method of "Learning Together" emphasizes cooperative learning, division of tasks, individual responsibilities, cooperation, both achieving the same results. Based on the perspective of Social Learning Theory, it can be understood that learning with the Learning Together method is a social situation that is built based on the function of personal factors, behavioral factors, and environmental factors that interact with interesting, demonstrative, and quality characteristics. This learning situation stimulates individual social activities and individual initiative as a real and integrated part of the group to complete group assignments based on the short story review components. Thus, individuals experience a more permanent formation because the process of formation arises from within themselves and is well organized. Through learning situations like this the ability possessed by students is not only proceeded in the level of individual awareness itself but through social dynamics that can lead to individual confidence in actualizing themselves and their ability to write short story reviewer texts. Thus, it can be obtained at the same level of ability in quality in the work of short story reviewer texts.